2015
DOI: 10.1038/srep17638
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effects of vitamin D treatment on bleomycin-induced pulmonary fibrosis

Abstract: Patients with pulmonary fibrosis often have low vitamin D levels, the effects of which are largely unknown. We here report that early vitamin D supplementation significantly reduced the severity of pulmonary fibrosis and inflammatory cell accumulationin in the bleomycin-induced pulmonary fibrosis mouse model on supplementary days 14, 21 and 28 (P < 0.001). Vitamin D supplementation also prevented some ultrastructural changes in response to bleomycin administration, including basement membrane thickening, inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…Ramirez et al demonstrated that vitamin D inhibited TGF-β-induced pro-fibrotic effects in lung fibroblasts and epithelial cells [ 33 ]. In addition, vitamin D treatment attenuated pulmonary fibrosis and associated cellular and ultra-structural changes induced by bleomycin in mice [ 38 ]. Due to the importance of inflammation and EMT in the development of pulmonary fibrosis, calcitriol can also inhibit bleomycin-induced early pulmonary inflammation and subsequent EMT in vivo [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ramirez et al demonstrated that vitamin D inhibited TGF-β-induced pro-fibrotic effects in lung fibroblasts and epithelial cells [ 33 ]. In addition, vitamin D treatment attenuated pulmonary fibrosis and associated cellular and ultra-structural changes induced by bleomycin in mice [ 38 ]. Due to the importance of inflammation and EMT in the development of pulmonary fibrosis, calcitriol can also inhibit bleomycin-induced early pulmonary inflammation and subsequent EMT in vivo [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…VDR is cited as the master regulator of the genomic-driven activation of fibroblasts, although its inhibition has been suggested to re-sensitize pancreatic cancer cells that became resistant to gemcitabine [174]. In any case, VDR activation achieves stromal restoration by inhibiting the TGF-β/Smad pathway that, as previously discussed, constitutes a key driver of fibroblastic activation [125,173,175]. With the goal of ramping up the activity of VDR, investigators introduced an analog of its ligand, which resulted in the suppression of inflammatory cytokines and growth factors, enhanced angiogenesis, and increased efficacy of therapeutics while significantly improving overall survival [176].…”
Section: Restoration Of Innate Stroma Characteristics Promises a Feasmentioning
confidence: 99%
“…Vitamin D treatment could prevent bleomycin-induced pulmonary fibrosis by delaying or suppressing ultrastructural changes, as well as by attenuating hydroxyproline accumulation and inhibiting myofibroblastic proliferation 3 . Vitamin D intake decreased COPD exacerbation and improved forced expiratory volume in one second (FEV1) in patients with severe and very severe COPD 4 .…”
Section: Introductionmentioning
confidence: 99%